Borrowing and Lending Agreements in the Civil Code and Islamic Economics - Nurul Yusro Sirait; Salwa Amelia Syafira; Sophia Harahap; Dewi Alesia Fitri (ISNU Sumatera Utara, 2025)
Borrowing and lending agreements are important legal instruments in socio-economic life. Agreements in the Civil Code are regulated in Book III concerning obligations. The definition of the limits of an agreement is regulated in Article 1313 of the Civil Code which states that; An agreement is an act by which one or more people bind themselves to one or more other people. In general, a person is declared negligent or in default because they do not fulfill the performance at all, the performance is not perfect, is late in fulfilling the performance and does what is prohibited in the agreement. This study aims to analyze the comparison between borrowing and lending agreements in the Civil Code (KUHPerdata) and the Sharia Economic Law Code (KHES). The research method uses comparative analysis. The results of the study show significant differences in rights and obligations, time periods, and legal recognition. This study contributes to the understanding of Sharia economic law and the Civil Code.